ENHANCING ADOLESCENTS’ SKILLS-ACQUISITION MINDSET FOR SUSTAINABLE ECONOMIC GROWTH IN EPE METROPOLIS USING VALUE RE-ORIENTATION COUNSELING SERVICES - OWOYELE, JIMOH WALE; OLUGBENRO, SOLOMON OLUSEGUN (Sokoto Educational Review, 2025)
In Epe Metropolis, a significant portion of the adolescent population faces challenges in recognizing and valuing the importance of skills acquisition. This issue poses a critical barrier to both individual development and the sustainable economic growth of the region. This study examined the effectiveness of value re-orientation counseling services in fostering a skills acquisition mindset among secondary school adolescents. A descriptive cross-sectional research design was employed. Eighty adolescents were selected using simple random sampling from three public secondary schools in Epe Metropolis, Lagos State, Nigeria, from a population of 1,171 senior school students aged 13 to 24 years. Data were collected using the "Adolescents’ Skills-Acquisition Mindset and Value Re-Orientation Counseling Services Questionnaire (ASAMVRCSQ)," with a reliability coefficient of .76. Descriptive and inferential statistics, including independent sample t-tests, were used to analyze the data. The practical relevance of value re-orientation counseling services was assessed using Hedges’ g effect size for unequivalent samples. Findings revealed a negative attitude among adolescents towards skills acquisition (Mean = 2.47) and a low level of awareness of value re-orientation counseling services among school adolescents (10.0%). Value re-orientation counseling services were found to be highly effective in changing adolescents’ attitudes towards skills acquisition (t(78) = 47.128, p < .05, Hedges’ g = 1.662). Recipients of value re-orientation counseling services exhibited a more positive mindset (Mean = 28.63, S.D= 3.517) than non-recipients (Mean = 18.19, S.D= 6.492). The study concluded that counseling for value re-orientation at the secondary school level is vital for supporting school adolescents’ development of a skills acquisition mindset. The researchers recommended that school counselors should consider utilizing value re-orientation counseling to identify students with practical skills potential and help cultivate the right attitudes and values necessary for skills acquisition. DOI: https://doie.org/10.0301/SER.2025340019